Obtaining World Fame from the Periphery. (3rd May 2020) - Heilbron, Johan
ABSTRACT: Although book translations are overwhelmingly made from English and a small number of other central languages, translations occasionally also flow in the opposite direction, i.e. from peripheral countries and languages to more central ones. This article explores the translation and international recognition of Dutch writers. It identifies a general pattern structured by three successive circuits of selection, diffusion, valorization and recognition. The first is the semi-official Dutch circuit outside of the Netherlands, socially based on Dutch-speaking groups abroad, dependent on Dutch foreign policy, and institutionally tied to embassies, institutes for Dutch culture, and university departments for Dutch language and literature. After having achieved some degree of visibility and recognition in this protected circuit, some writers succeed in obtaining access to a second circuit consisting of the respective national literary fields of the receiving countries. Selection and recognition here depend on editors, publishers, critics, and audiences of the receiving country. The last circuit – the one in which international fame can be obtained – represents an even more selective, transnational universe institutionally tied to world book fairs, international publishing houses, and international prizes. The process by which writers can pass from the first to the second and third circuit is, for most, one of progressive elimination.